Of the Deepest Shadows and the Prisons of Fire - Nwankwo, Chimalum Moses, 1949- (Book collections on Project MUSE., 2010)
Of the Deepest Shadows and The Prisons of Fire is a literary canvas of leaders who have affected humanity in very serious and unquestionable ways. The core of this artistic engagement is the destiny of the black world. There are tangential departures into territories with crises the world cannot afford to ignore. The poet visits each leader, living or dead, with equal passion. His curious brush is delicate, ecstatic, melancholic or even celebratory depending on what image or circumstance he pans into view. This corpus comes with the characteristic anguish and tenderness of a very sensitive and.